Development of Cyclic Propagation Kinetics for Modeling the Nitroxide-mediated Radical Copolymerization of Styrene - Divinylbenzene - Leandro G. Aguiar (2013)
A kinetic model including the cyclic propagation (cyclization) is proposed for the nitroxide-mediated radical copolymerization of styrene-divinylbenzene. The method involves a balance of sequences of units, which connect a radical center and a pendant double bond present in the same polymer chain. The rate constant for cyclization was considered a function of the sequence length. Good agreement between the model predictions and experimental data for solution and suspension controlled copolymerizations was found. The rate constant of cyclization for the smallest ring (3 monomeric units) was estimated to be 700s(-1) at 90 degrees C, and the activation energy was estimated to be 32500calmol(-1).